Fragmentary Theory of Secularization and Religionization — Changes in the Family Structure as a Case Study. Issue 2 (24th November 2016) - Fisher, Netanel
Abstract: The central claim of this article is that the multi-dimensional changes in the modern family structure may be explained as a manifestation of the simultaneous processes of secularization and religionization. On the one hand, the rising acceptance of secular alternatives to the traditional family structure indicates that modernization processes weaken religious behavior and authority, as the classical secularization thesis has claimed. On the other hand, ongoing loyalty to the religious family patterns, and even their relative intensification, reflect the opposite trend. Serving as a case study, the changes in the Israeli religious family structure — reflected by civil marriage, cohabitation, and out-of-wedlock children — clearly illustrate how modernization generates horizontal and vertical fragmental processes in which religion and secularism supplement as well as compete with each other, creating an increasingly divided society in which religiosity and secularism flourish side by side among various groups and within distinct realms.